Immobilization of lipase B from Candida antarctica on epoxy‐functionalized silica: characterization and improving biocatalytic parameters. Issue 1 (20th June 2017) - de Souza, Stefânia P; de Almeida, Rayza AD; Garcia, Gabriel G; Leão, Raquel AC; Bassut, Jonathan; de Souza, Rodrigo OMA; Itabaiana, Ivaldo
Abstract: BACKGROUND: In this work, lipase B from Candida antarctica (CaLB) was immobilized on Purolite® ECR8205F, Purolite® ECR8214F and Immobead® IB150 P epoxy resins with no modification to their surfaces. Biocatalysts were evaluated for thermal stability and applied in reactions of hydrolysis, esterification and the synthesis of glyceryl carbonate by transesterification with dimethyl‐carbonate both with glycerol and Macauba oil as well as dynamic kinetic resolution of α‐methylbenzylamine, all of them compared with commercial Novozyme 435®. RESULTS: Protein desorption of the biocatalysts with Triton X‐100 showed that lipase was immobilized by covalent single‐bond type binding. The immobilization efficiencies were 55.1% for the biocatalyst 8205, 57.1% for 8214, and 14.9 for the 150P, demonstrating the intense effect of surface and material composition on lipase immobilization. The biocatalysts also showed higher initial velocities of esterification and hydrolysis reactions as well as higher thermal stability than Novozyme 435®. On glycerol carbonate synthesis, conversion of 97% and selectivity higher than 99% was demonstrated by enzyme 8214, similar to Novozyme 435®. On kinetic dynamic resolution, conversions higher than 94% and and enantiomeric excesses greater than 90% were also depicted. CONCLUSION: Compared with commercial preparation Novozyme 435®, the novel biocatalysts obtained by immobilization on new epoxy resins demonstrated protein loads about 10‐fold lower and higher specific activity. In all reactions performed, competitive performances were found, demonstrating high potential for industrial applications. © 2017 Society of Chemical Industry